Direct-acting antiviral treatment for HIV/HCV patients in safety net settings: patient and provider preferences. Issue 11 (2nd November 2019) - Shumway, Martha; Luetkemeyer, Anne F.; Peters, Marion G.; Johnson, Mallory O.; Napoles, Tessa M.; Riley, Elise D.
ABSTRACT: HIV/HCV coinfected patients are a priority for direct acting antiretroviral (DAA) treatment, yet barriers to treating vulnerable patients persist. This study surveyed safety net clinic patients and providers to quantify their preferences for DAA treatment and prioritize modifiable barriers. Preferences were assessed using best-worst scaling. General linear mixed models were used to determine whether attributes differed in importance and whether patients and providers valued attributes differently. 158 HIV/HCV coinfected patients and 49 providers participated. Patients and providers had strong preferences for treatment within the medical homes where patients receive HIV care. Support such as reminders and advice numbers were also important, but were more important to providers than patients. Providers identified lack of insurance coverage for DAA as the most significant barrier. Providers rated HIV primary care providers as best suited to deliver DAA to HIV+ patients. Addressing structural barriers is essential for increasing DAA treatment in safety net settings.